2011
DOI: 10.1115/1.4002918
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Filter Smoke Number and Elemental Carbon Mass From Partially Premixed Low Temperature Combustion in a Direct-Injection Diesel Engine

Abstract: Partially premixed low temperature combustion (LTC) is an established advanced engine strategy that enables the simultaneous reduction of soot and NO, emissions in diesel engines. Measuring extremely low levels of soot emissions achievable with LTC modes using a filter smoke meter requires large sample volumes and repeated measurements to achieve the desired data precision and accuracy. Even taking such measures, doubt exists as to whether filter smoke number (FSN) accurately represents the actual smoke emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Soot mass emissions from the PPCI engine were measured using an AVL Microsoot photoacoustic analyzer and an AVL 415S Smoke Meter was used for the RCCI engine. Though smoke meter measurements have been shown to be comparable to soot mass concentration even at very low levels found in LTC modes (Northrop et al 2011b), such information for the photoacoustic analyzer is sparse. Future work is required to validate the accuracy of Microsoot measurements for low elemental carbon LTC particles.…”
Section: Particle Emissions Measurement and Analysismentioning
confidence: 99%
“…Soot mass emissions from the PPCI engine were measured using an AVL Microsoot photoacoustic analyzer and an AVL 415S Smoke Meter was used for the RCCI engine. Though smoke meter measurements have been shown to be comparable to soot mass concentration even at very low levels found in LTC modes (Northrop et al 2011b), such information for the photoacoustic analyzer is sparse. Future work is required to validate the accuracy of Microsoot measurements for low elemental carbon LTC particles.…”
Section: Particle Emissions Measurement and Analysismentioning
confidence: 99%
“…28 Since light-absorbing organics such as polycyclic aromatic hydrocarbons (PAHs) can alter reflectance, 29 low soot and highly condensable aromatic hydrocarbon (HC) concentrations in the exhaust can make interpretation of FSN difficult. For such conditions, Northrop et al 30 found that using a sample volume of 3000 mL over an FSN range of 0.02-1.5 was . (a) NOx and soot formation in local equivalence ratio (F) versus local temperature space and (b) conceptual model of mixing limited diesel combustion illustrating the locations of NOx and soot formation 4 adapted from Kitamura et al 5 adequate for correlating FSN to soot mass for premixed charge compression ignition (PCCI) combustion with conventional fuels and biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Filter based light absorption requires significant calibration and corrections and may also suffer from organic particulate and particle size biases Bond et al, 1999;Kondo et al, 2009;Lack et al, 2008a;Nakayama et al, 2010). A common technique for measuring the opacity created by engine exhaust smoke, the filter smoke number (FSN), is a filterbased absorption method that requires substantial empirical corrections to derive BC mass (Northrop et al, 2011). Uncertainties on mass derived from FSN measurements are therefore dependent on the fit to empirical data.…”
Section: Definition and Measurement Of Black Carbonmentioning
confidence: 99%
“…The FSN is a unitless number derived from filter based light absorption. The measurement technique has known biases (Northrop et al, 2011) that can, in principle, be corrected (Christian et al, 1993) and then translated into BC concentrations. We apply the Christian et al (1993) correction to all the FSN data in this review to produce a BC FSN mass emission factor.…”
Section: Toa Ec -Fsn Bcmentioning
confidence: 99%